Afghan’s Settlements, Terrorism, and Internal Security Nexus: Correlation Analysis of Pakistan - Nazirullah (Journal of Peace, Development and Communication, 2021)
Pakistan is hosting millions of Afghan refugees since the Soviet invasion in Afghanistan back in the 1980s. The multifarious issue of Afghan refugees’ burdens Pakistan's economy and raise serious security concerns. This research provides the need assessment of the Afghan refugees' and discourse on challenges for the security of Pakistan. In line with it, the alternative strategies for the welfare of Afghans refugees are also highlighted and investigated to delineate the plans executed by the Pakistan government for protection of Afghan refugees. Methodologically, the quantitative method has been adopted. The purposive sampling technique was used, and the sample size of the study was (N=316). Collected data was analyzed through SPSS V. 21, to explore the relationship between variables. Pearson-Product Moment Correlation test was applied, and predictions were made through regression analysis. The significant findings of the study revealed that there was a strong negative correlation among basic needs, perception of good strategies, and Pakistan’s security problems. It was also found that terrorism and Pakistan's security problems have a strong positive correlation. Nevertheless, fulfilling the basic needs of Afghan refugees is more likely to reduce Pakistan’s security problems. Based on the findings, it is concluded that peace in Afghan is investable to sustain peace in the entire region. Social support programs indeed to extend for Afghan refugees and State also may provide a roadmap to their resettlement in Afghanistan in the long run. Keywords: Afghan peace, terrorism, afghan refugees, Pakistan’s security.